(untitled) (Research Announcements "Heritage BG", 2025)
The paper presents a brief scientific study of the capabilities of the APOGEE software platform to facilitate the automated creation of an educational video maze game. It presents the developed within Heritage BG project experimental educational video maze game dedicated to the work and legacy of Bulgarian rebel Valchan Voivoda and their impact on the historical development of Bulgaria in the first half of the 19th century. References: Abt 1987: Abt, Clark C. Serious Games. University Press of America. Bontchev 2015: Bontchev, Boyan. Serious Games for and as Cultural Heritage. In: Digital Presentation and Preservation of Cultural and Scientific Heritage, V, 43-58. Bontchev, Vassileva, Dankov 2019: Bontchev, Boyan, Vassileva, Dessislava and Yavor Dankov. The APOGEE Software Platform for Construction of Rich Maze Video Games for Education. In: Proceedings of ICSOFT’2019, Ed. by M. van Sinderen and L. Maciaszek, INSTICC, 491-498. Deterding, Khaled, Dixon, Nacke 2011: Deterding, Sebastian, Khaled, Rilla, Dixon, Dan and Lennart Nacke. From Game Design Elements to Gamefulness: Defining Gamification. In: MindTrek, 9-15. Gee 2009: Gee, James. Games, Learning and 21st Century Survival Skills. In: Journal for Virtual Worlds Research, 2(1). Gee 2003: Gee, James. What Video Games Have to Teach us About Learning and Literacy. In: Journal of Computer Entertainment, Vol. 1, 20-28. Girard, Écalle, Magnan, 2013: Girard, C., Écalle, Jean and Annie Magnan. Serious Games as New Educational Tools: How Effective are They? A Meta-analysis of Recent Studies. In: Journal of Computer Assisted Learning, 29, 207-219. Kirriemuir, McFarlane 2004: Kirriemuir, John and Angela McFarlane. Literature Review in Games and Learning, Futurelab Series, Report 8. Michael, Chen 2006: Michael, David and Sande Chen. Serious Games: Games that Educate, Train and Inform. Boston, MA. Thomson Course Technology. Paunova-Hubenova 2019: Paunova-Hubenova, Elena. Didactic Mini Video Games – Students’ and Teachers’ Point of View. In: CBU International Conference Proceedings, Vol. 7, 552-558. Prensky 2002: Prensky Marc. The Motivation of Game Play. The Real Twenty-first Century Learning Revolution. In: On the Horizon, 10(1), 5-11. Ritterfeld, Weber 2006: Ritterfeld, Ute and Rene Weber. Video Games for Entertainment and Education. In: Playing Video Games: Motives, Responses, and Consequences, Lawrence Erlbaum Assoc. Publ. 24(1), 399-413. Salen, Zimmerman 2004: Salen, Katie and Eric Zimmerman. Rules of Play: Game Design Fundamentals. MIT Press, Cambridge, USA. Terzieva, Paunova-Hubenova, Bontchev 2018: Terzieva, Valentina, Paunova-Hubenova, Elena and Boyan Bontchev. Identifying the User Needs of Educational Video Games in Bulgarian Schools. In: Proceedings of ECGBL’18, 687-695.